ISSUES OF IMPROVING CURRENT ASSET ACCOUNTING AND AUDIT - Mavlanova Dilrabo Uktamovna (Web of Journals Publishing, 2025)
This article discusses the improvement of current asset accounting and audit. Accounting and reporting, their improvement should be aimed at providing the management system at all levels with reliable and trustworthy information sufficient to justify management decisions - investment, financial, production, current and strategic, local and global.
Keywords: Audit, audit activity, audited entity, accounting, international auditing standards, self-regulatory organizations, internal control.